2009
DOI: 10.1007/s00253-009-2314-z
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of polymerase chain reaction with thermostable inorganic pyrophosphatase from hyperthermophilic archaeon Pyrococcus horikoshii

Abstract: An inorganic pyrophosphatase (PPases) was cloned from the hyperthermophilic archaeon Pyrococcus horikoshii and was expressed in and purified from Escherichia coli. The recombinant inorganic pyrophosphatase (PhPPase) exhibited robust catalytic activity of the hydrolysis of pyrophosphate into two orthophosphates at high temperatures (70 degrees C to 95 degrees C). Thermostable pyrophosphatase activity was applied into polymerase chain reaction (PCR) due to its ability to push chemical equilibrium toward the synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…PPAs prevent the accumulation of PP i during DNA sequencing reactions (3,4), PCR (5), and single-base extension (SBE) reactions (6). PPAs are also used to increase the yields of RNA by in vitro transcription (7) and of GDP-modified sugars by enzymatic synthesis (8,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PPAs prevent the accumulation of PP i during DNA sequencing reactions (3,4), PCR (5), and single-base extension (SBE) reactions (6). PPAs are also used to increase the yields of RNA by in vitro transcription (7) and of GDP-modified sugars by enzymatic synthesis (8,9).…”
mentioning
confidence: 99%
“…PPAs of the class A type are not associated with the membrane and are widespread in all domains of life, including Archaea. Class A type PPAs of hyperthermophilic archaea are already used in PCR and DNA sequencing reactions (4,5). In contrast, PPAs with DHHA2 domains (IPR004097) and PPAs of the PP i -energized H ϩ pump (IPR004131), Mn 2ϩ -dependent (IPR022934), and PpaX-type (IPR023733) families are not as widely distributed in archaea and/or can be difficult to purify due to their association with membranes.…”
mentioning
confidence: 99%
“…Literature reports of increased PCR yield when a thermostable inorganic pyrophosphatase (IPPase) was included in the reactions inspired us to test this enzyme in a qPCR series to see if we could drive the reaction forward by degrading the pyrophosphate, one of the two products of the chain reaction [17], [18]. Unexpectedly, the addition of IPPase reduced the apparent reaction yield ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…PPase activity has been found to be associated with GTases of other RNA viruses such as Bluetongue virus and Avian reovirus [9,10] and thus the PPase activity may be an intrinsic activity of multifunctional L protein. The role Virus Genes of PPase activity in replication has been suggested across eukaryotic and prokaryotic species [11] and work on Pyrococcus horikoshii PPase showed that it enhances DNA synthesis with Taq polymerase in vitro [12]. Genomic colocalization of PPase and polymerase gene in Thermococcus onnurineus [13] and the activation of these genes by Fig.…”
Section: L-rtpase Domain Possesses Tripolyphosphatase Activitymentioning
confidence: 97%